Are FE/HE Staff ICT Competent? A report from the tRISSt research project - Garratt, Dean; Gilroy, Peter; Saxon, Diane; Cairns, Clive (Proceedings of the International Conference on Networked Learning, 2002)
In this paper, we describe the finding of the first phase of the Recognition of ICT Skills of Staff (tRISSt) project, in which we raise questions about the assumption that FE and HE staff have the appropriate ICT capabilities to make use of the opportunities provided by networked learning to develop teaching and learning in their students.